2020
DOI: 10.1200/jgo.20.00005
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, Clinical, and Pathologic Features of Patients With Cutaneous Melanoma: Final Analysis of the Brazilian Melanoma Group Database

Abstract: PURPOSE National epidemiologic data on melanoma are scarce in Brazil. The current work presents final demographic, clinical, and pathologic results from the Brazilian Melanoma Group database to detail how patients with melanoma present at diagnosis. METHODS The online database includes patients diagnosed between 1982 and 2015 and evaluated at their centers of origin between 2001 and 2016. The primary objective was to describe the demographic, clinical, and pathologic characteristics of the patients, and second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
2
3
1
7
Order By: Relevance
“…The predominance of cases in this age group was also found in a retrospective study conducted at the Federal University of São Paulo by Ferreira et al, in 2018. (25) The present study identified that 97.87% of the subjects with cutaneous melanoma were white-skinned, similar to studies carried out in the country by Wainstein et al (2020) (22) (91%) and Costa et al (2019) (26) (93.1%). In addition, the strong association of fair skin with the development of cutaneous melanoma has already been identified in other works, as in the prospective study by Olsen et al (2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The predominance of cases in this age group was also found in a retrospective study conducted at the Federal University of São Paulo by Ferreira et al, in 2018. (25) The present study identified that 97.87% of the subjects with cutaneous melanoma were white-skinned, similar to studies carried out in the country by Wainstein et al (2020) (22) (91%) and Costa et al (2019) (26) (93.1%). In addition, the strong association of fair skin with the development of cutaneous melanoma has already been identified in other works, as in the prospective study by Olsen et al (2019).…”
Section: Discussionsupporting
confidence: 91%
“…In a study conducted in São Paulo by Melo et al ( 2018), (21) a slight predominance of cases was found among females (51.9%). Furthermore, in 2020, Wainstein et al (22) showed a majority of cases among women (57%), in addition to studies carried out in Brusque, SC (12) and Curitiba, PR (23) that also detected predominance of women (56.6% and 58.9%, respectively).…”
Section: Discussionmentioning
confidence: 92%
“…No presente Serviço, essa taxa manteve-se estável e possivelmente o pico verificado no ano de 2008 resultou da maior divulgação do tema e da busca de orientação médica decorrente de polêmicas geradas pela Lei que culminou posteriormente com a proibição de bronzeamento artificial no país. A faixa etária média de 57,3 anos dos pacientes avaliados nesse hospital foi similar a investigações conduzidas no Sul, Sudeste e Centro-Oeste brasileiros 5,[11][12][13][14][15][16][17] , bem como na América do Norte e Europa [18][19][20] . No entanto, chama a atenção que a maior parte da presente casuística encontrava-se em idade produtiva inferior a 60 anos, com possíveis repercussões socioeconômicas, perda na produtividade e na qualidade de vida.…”
Section: Discussionunclassified
“…A raça branca compreendeu 98,6% dos casos, sendo explicada pela miscigenação racial regional e também pela maior susceptibilidade da pele clara à agressão pelos raios ultravioleta. Mesmo nos países com menor prevalência de população branca, esta é ainda a mais acometida 1,2,11,14,17,20,22 .…”
Section: Discussionunclassified
“…The incidence of cutaneous malignant melanoma has been increasing over the past 50 years in populations that are predominantly fair-skinned [ 1 ]. Although rates have stabilized recently in several parts of the world including Australasia and North America, they continue to rise in most European and South American countries [ 1 3 ]. Exposure to ultraviolet radiation, especially intermittent sun exposure resulting in sunburn, is the main environmental factor associated with increased melanoma risk [ 4 ].…”
Section: Introductionmentioning
confidence: 99%